AN EMPIRICAL STUDY ON APPLICATIONS, FEATURES, AND CHALLENGES OF M-BANKING SERVICES IN INDIA - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2021)
Mobile banking refers to the usage of mobile phones to perform banking services online. Mobile banking can perform balance checking, fund transfers, electronic bill payments, P2P payments, monitoring transactions; UPI (Unified Payments Interface) payment system is one of the most popular payment systems. UPI system power multiple bank accounts into one single mobile application; it merges numerous banking features into one hood. This study has also explored the issues and challenges faced by the customers in the mobile banking systems that are critical in the adoption by the customers in using the mobile banking system. This study identifies some of the issues related to banks, mobile applications, security, and telecom service operators. The mobile banking system faces the operation of smart mobile phones, security and privacy, standardization of services, and customization. 212 respondents were collected through a "Standard questionnaire" created on a five-point interval scale.